Post Hatch Development of Alkaline Phosphatase Activity in the Broiler Small Intestine - Belabbas , Hadj; Melizi, Mohamed; Benkhaled, Abderrahim; Adili, Nezar (International Journal of Poultry Science, 2015)
This study was aimed to determine the alkaline phosphatase activity following time course (days) in the intestine of broilers. We used a sample of 54 subjects of broilers from hatching period to 56th day of age. Our finding showed a significant increase in the alkaline phosphatase activity at various levels in the different intestinal segments during the first two weeks of life and then decreased significantly with age (p<0.05). Moreover, alkaline phosphatase activity was higher in the duodenum and jejunum than in the ileum over the period examined. We concluded that alkaline phosphatase as a marker of enterocyte maturation, has a high enzymatic activity in the duodenum and jejunum of broilers.